Accuracy of biomarkers obtained from cone beam computed tomography in assessing the internal trabecular structure of the mandibular condyle - Ebrahim, Fouad H.; Ruellas, Antonio C. O.; Paniagua, Beatriz; Benavides, Erika; Jepsen, Karl; Wolford, Larry; Goncalves, Joao Roberto [UNESP]; Cevidanes, Lucia H. S. (Elsevier B.V., 2017)
Objective. The aim of this study was to validate the ability of cone beam computed tomography (CBCT) to measure condylar internal trabecular bone structure and bone texture parameters accurately. Study Design. Sixteen resected condyles of individuals undergoing temporomandibular joint replacement were collected and used as samples. These condyles were then radiographically imaged by using clinically oriented dental CBCT and research oriented micro-computed tomography (micro-CT). The CBCT scans were then compared with the gold standard micro-CT scans in terms of 21 bone imaging parameters. Descriptive histologic investigation of the specimens was also performed. Results. Significant correlations were found for several imaging parameters between the CBCT and micro-CT images, including trabecular thickness (r = 0.92), trabecular separation (r = 0.78), bone volume (r = 0.90), bone surface area (r = 0.79), and degree of anisotropy measurements (r = 0.77). Conclusions. Measurements of trabecular thickness, trabecular separation, bone volume, bone surface area, and degree of anisotropy obtained from high-resolution dental CBCT images may be suitable bone imaging biomarkers that can be utilized clinically and in future research.